An ethnography of the Mandela Peace Park senior citizens food garden in Mamelodi Township Tshwane : a social critique of the economism in contemporary urban agriculture policies and projects - Krige, Detlev (University of Pretoria, 2019)
Dissertation (MSocSci)--University of Pretoria, 2018.